Rational design of multifunctional properties for styrene-butadiene rubber reinforced by modified Kevlar nanofibers. (1st June 2019) - Chen, Yang; Yin, Qing; Zhang, Xumin; Zhang, Wanqi; Jia, Hongbing; Ji, Qingmin; Yang, Fufeng; Rui, Xiaoting
Abstract: In this work, a facile and effective approach is developed to obtain the water-dispersible Kevlar nanofibers (KNFs) by modifying KNFs with the assistance of epichlorohydrin (ECH). And the ECH-modified KNFs (m-KNFs) are firstly utilized to prepare styrene–butadiene rubber (SBR)/m-KNFs nanocomposites through latex co-coagulation method. The multifunctional properties of SBR/m-KNFs nanocomposites are thoroughly investigated. It is confirmed that m-KNFs have strong interactions with SBR via π-π stacking, which can generate huge enhancement on the performance of SBR nanocomposites. For example, the tensile strength, tear strength and the maximum decomposition temperature of SBR filled with 7 phr (parts per hundred rubber) m-KNFs are increased by 576%, 202% and 13.1 °C, respectively, compared with those of neat SBR. Meanwhile, the presence of m-KNFs has also improved the dielectric constant of SBR nanocomposites. This work provides a new insight into the fabrication of multifunctional KNFs-based rubber composites.